Reconstruction of Character Education Based on Prophetic Education Philosophy in The Digital Age - Abdullah Haryono; Aldereza Lidiya Mazyuna; Sri Yulia Yuliani; Sofyan Sauri (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2025)
This study examines the reconstruction of character education based on the philosophy of prophetic education in the digital era, which serves as a new alternative in the field of education. The main challenge currently faced by the education sector is how to maintain a balance between technological advancement and the development of strong character. The implementation of character education grounded in the philosophy of prophetic education in the digital age is expected to produce a generation that is not only intelligent but also possesses strong moral character. This study employs a library research method. Library research is a data collection technique aimed at gathering information from written documents, both official records and other scholarly sources. Once the data is collected, it is processed by analyzing the existing information to address the research problem. The content analysis method is used to interpret ideas and identify their relevance to the issues being investigated. The results of this study indicate that the reconstruction of character education based on the philosophy of prophetic education in the digital era represents one of the innovative ideas to help the Indonesian education system evolve amidst the challenges of the digital age.